MODIFIKASI MEJA KERJA MENURUNKAN BEBAN KERJA PEKERJA KERAJINAN LOGAM DI KABUPATEN TABANAN BALI - Adiatmika, I Putu Gede (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2010)
Ironwork industries is the major work for the employee at Tabanan Bali. Export of product could give more income for the goverment and human life. Many of order make them work overtime to fill the target by working overtime. The impact was more stress and cause workload increased, but productivity decreased. An effort to decrease emplo-yee’s workload is one of the program in order to reduce the stress through ergonomic intervention. Ergonomic analysis found that there was work posture problem caused by low of work table sgtation. Improvement of work table station was aim to decrease the workload. This experiment was conducted on January – June 2006 at ironwork handicraft employee at Tabanan Regency. Design of research is pre-post group design and treat-ment by subject. Intervention was done through modification of work table height that was designed based on elbow height. Subject were 30 skill employee from 6 workshops. Data assessed were heart rate, elbow height, work heart rate using 10 pulse method and ana-lyzed by t-test. The result showed that an impact of table modification to decreased of workload (p > 0.05). The magnitude of impact was 27.26 %. It,s suggested that the em-ployee should use table modification regularly through adaptattion process for optimum effect.